Mesophase pitch prepared through catalysis of metal-free superacid and preparation method of mesophase pitch

By using a low-temperature prepolymerization-high-temperature heat condensation method without metallic superacid catalysts, the problems of catalyst corrosion on equipment and metal residues were solved, and high-purity and high-performance mesophase asphalt were prepared, which improved experimental safety and product performance.

CN119570514APending Publication Date: 2025-03-07BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410870139.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing catalytic polycondensation method for preparing mesophase asphalt has problems such as catalyst corrosion on equipment and metal residues, which affects product performance and experimental safety.

Method used

Metal-free superacid is used as a catalyst to prepare mesophase asphalt through two-step polymerization of low-temperature prepolymerization-high-temperature heat condensation. The process is carried out in a glass reactor to avoid equipment corrosion and remove catalyst and metal ions by neutralizing lye and washing with water to ensure no metal residue.

Benefits of technology

It realizes efficient catalytic formation of mesophase asphalt under low temperature conditions, avoids equipment corrosion and metal residues, improves the purity and performance of the product, and enhances the safety of the experiment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004921914490000091
    Figure BDA0004921914490000091
  • Figure HDA0004921914570000011
    Figure HDA0004921914570000011
  • Figure HDA0004921914570000012
    Figure HDA0004921914570000012
Patent Text Reader

Abstract

The invention discloses mesophase pitch prepared through catalysis of metal-free superacid and a preparation method of the mesophase pitch, and belongs to the technical field of high polymer materials. Comprising the following steps: in an inactive atmosphere, contacting metal-free superacid serving as a catalyst with polycyclic aromatic hydrocarbon, carrying out prepolymerization reaction to obtain a prepolymerization system, adding alkali liquor until the prepolymerization system is neutral, washing with water to remove the catalyst and metal ions, distilling to remove small molecules, placing the product in a closed container in the inactive atmosphere, and carrying out vacuum drying to obtain the polycyclic aromatic hydrocarbon. And carrying out a thermal polycondensation reaction to prepare the mesophase pitch. According to the preparation method, the metal-free superacid can be conveniently removed from the system, the subsequent reaction equipment cannot be corroded, the experiment operation requirement is low, the experiment safety is high, the product without the catalyst basically has no metal residue, the method has great advantages in synthesis of high-purity products, and compared with a metal catalysis system, the method has the advantages that the cost is low, and the method is suitable for industrial production. The content of the obtained intermediate phase is higher, the intermediate phase distribution is more uniform, and the intermediate phase is of a wide-area structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a mesophase asphalt prepared by metal-free superacid catalysis and a preparation method thereof, belonging to the technical field of polymer materials. Background Art

[0002] Mesophase is a disc-shaped nematic liquid crystal structure, which is composed of parallel arrangement of planar aromatic macromolecules with birefringence characteristics. Mesophase pitch is a polymer composed of various polycyclic aromatic hydrocarbons, with a relative molecular weight between 370-2000, and is formed by physical and chemical reactions of organic matter under certain conditions. The formation of mesophase is related to the size of aromatic molecules, the planar regularity of molecules and the distribution of carbon atoms in molecules. To form an asphalt product with few defects and complete spherical development, aromatic molecules with high aromatic carbon content and uniform composition should be selected. Mesophase pitch has excellent mechanical properties due to its orderly stacking structure and is considered to be an excellent precursor of high-performance carbon materials. For example, mesophase pitch-based carbon fibers have extremely high Young's modulus, excellent axial resistivity, thermal conductivity and good high temperature corrosion resistance, and are high-performance industrial carbon products. Therefore, the preparation and development of mesophase pitch is of great significance to high-performance carbon materials.

[0003] Due to the large variety of raw materials for preparing mesophase asphalt, the properties of the generated mesophase asphalt products vary greatly. When synthesizing mesophase asphalt, different preparation methods should be adopted according to the structural characteristics of different raw materials. The direct thermal polycondensation method is to directly heat treat the raw materials to prepare mesophase asphalt. The temperature required for the direct thermal polycondensation reaction is high, the reaction is more violent, and the degree of polymerization is difficult to control, resulting in a sharp increase in the viscosity of the system, uneven distribution of the mesophase composition, and it is difficult to obtain a low-temperature spinnable product. The co-carbonization method is to mix the co-carbonizing agent with the raw materials and carbonize the mixture at high temperature to prepare the mesophase asphalt. Compared with the direct thermal polycondensation method, the co-carbonization method is easier to generate asphalt products with large watershed texture and high mesophase content, but it is necessary to find a suitable co-carbonizing agent. The catalytic polycondensation method is to add a certain catalyst to the aromatic raw material and prepare the mesophase asphalt by catalytic polymerization. The catalytic polycondensation method first performs catalytic polymerization at low temperature and then performs high-temperature polycondensation reaction, which can reduce the reaction temperature and time of synthesizing mesophase asphalt and save process costs. The catalytic aromatic molecules belong to cationic polymerization. Commonly used catalysts include HF / BF3, AlCl3, etc.

[0004] In the catalytic polycondensation reaction, HF / BF3 is selected as a catalyst, and a product with excellent performance can be obtained through low-temperature prepolymerization-high-temperature polycondensation in two steps, and HF / BF3 can be removed from the product by distillation, and there is no catalyst residue, which will not affect the product quality. As reported in the literature Korai Y, Nakamura M, Mochida I, et al. Mesophase pitches prepared from methylnaphthalene by the aid of HF / BF3. Carbon, 1991, 29 (4): 561-567, and the literature Mochida I, Shimizu K, Korai Y, et al. Mesophase pitch catalytically prepared from anthracene with HF / BF3. Carbon, 1992, 30 (1): 55-61, Korai Y et al. used a variety of aromatic hydrocarbons as raw materials and HF / BF3 as a catalyst to prepare a mesophase pitch with low softening point and good spinnability. Another example is Zheng Jiaming, Wang Chengyang, Ruan Xiangquan, etc. Preparation of naphthalene pitch and mesophase pitch by catalytic polycondensation [J]. Journal of Tianjin University, 1995 (2): 215-220. According to the literature, Zheng Jiaming and others used naphthalene as raw material and HF / BF3 as catalyst to generate isotropic naphthalene pitch. The obtained product contained a large amount of saturated hydrogen. The mesophase pitch prepared with this as raw material has good performance and can be used to manufacture carbon fiber. Selecting HF / BF3 as a catalyst can prepare mesophase pitch with excellent performance, but during the reaction, HF / BF3 will corrode the synthesis equipment made of metal, glass, silicon and other materials, causing experimental safety problems and high requirements for experimental equipment and experimental operation. Selecting AlCl3 as a catalyst, the mesophase pitch prepared by two-step polymerization can retain the branched structure in the raw material, and the obtained product has good low-temperature spinnability. For example, in the document Mochida I, An KH, Sakanishi K, et al. Preparation of nitrogen-rich pitches from diazanaphthalenes using AlCl3. Carbon, 1996, 34(5): 601-608, Mochida I et al. used naphthalene and ethylene tar as raw materials and AlCl3 as catalyst to generate oligomers at low temperature. After removing the catalyst with 0.1 mol / L hydrochloric acid solution, they obtained an intermediate phase pitch with good spinnability through thermal polycondensation.Compared with HF / BF3 catalysis, AlCl3 as a catalyst will not affect the experimental equipment, but the metal in the product will form oxides, hydroxides and other compounds after alkaline-acid washing. After repeated alkaline and acid washing, the aluminum compounds in the system cannot be completely removed, and the content is about 4.5%. The trace amount of metal residues in the system will affect the mechanical properties of the product. In the spinning process of asphalt products, aluminum compounds may react with components in the system, resulting in spinning difficulties and uneven fiber structure; the presence of aluminum compounds will also affect the rate and degree of subsequent pre-oxidation reactions, thereby affecting the pre-oxidation effect of the fiber; in the carbonization process, the residual aluminum elements in the system may generate aluminum oxide, which will destroy the structure of the carbonized product and reduce its mechanical properties; in the final asphalt-based carbon product, the presence of aluminum compounds will reduce the purity of the carbon product and may affect its electrical and thermal conductivity.

[0005] Therefore, there is an urgent need for a method for preparing mesophase asphalt by catalytic polycondensation that does not cause corrosion to equipment and has no metal residue. Summary of the invention

[0006] In order to solve the problems and shortcomings of catalyst corrosion to equipment and residual metal in the catalytic polycondensation to prepare intermediate phase asphalt in the prior art, the present application provides an intermediate phase asphalt prepared by metal-free superacid catalysis and a preparation method thereof, utilizing the fact that superacids have strong acidity and have good catalytic effects in many reactions requiring strong protonation, and that metal-free superacids can be easily removed from the system. The intermediate phase asphalt is prepared by low-temperature prepolymerization, quenching and decatalysis, and high-temperature polymerization of asphalt raw materials in a glass reactor using metal-free superacid catalysis. The preparation process will not corrode the equipment for subsequent reactions, and there is basically no metal residue in the reaction system, which will not affect subsequent reactions and even the performance of the final product, and has great advantages in synthesizing high-purity products.

[0007] This application adopts the following technical solutions:

[0008] According to one aspect of the present application, a method for preparing mesophase asphalt by metal-free superacid catalysis is provided, comprising the following steps:

[0009] S1. In an inactive atmosphere, a metal-free superacid is contacted with a condensed aromatic hydrocarbon as a catalyst to carry out a prepolymerization reaction to obtain a prepolymerization system;

[0010] S2, adding alkali solution to the prepolymerization system of step S1 until the prepolymerization system is neutral, then washing with water to remove the catalyst and metal ions, and distilling to remove small molecules;

[0011] S3. In an inert atmosphere, placing the prepolymerization system treated in step S2 in a closed container to carry out a thermal polycondensation reaction to obtain the mesophase asphalt.

[0012] Optionally, in step S1, the metal-free superacid is selected from at least one of fluorosulfonic acid, chlorosulfonic acid, trifluoromethanesulfonic acid, and carborane acid;

[0013] Optionally, the amount of the metal-free superacid used is 3% to 30% by weight of the condensed aromatic hydrocarbon.

[0014] Optionally, the amount of the metal-free superacid is selected from any value among 3%, 5%, 10%, 15%, 20%, 25%, 30% by weight of the condensed aromatic hydrocarbon, or any range between the two.

[0015] Preferably, the amount of the metal-free superacid used is 10% to 15% by weight of the condensed aromatic hydrocarbon.

[0016] Optionally, in step S1, the conditions of the prepolymerization reaction include: a reaction temperature of 80° C. to 250° C., and a reaction time of 4 h to 48 h.

[0017] Optionally, in step S1, in the conditions of the prepolymerization reaction, the reaction temperature is selected from any value of 80°C, 100°C, 120°C, 140°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or any range between two thereof.

[0018] Preferably, in step S1, the prepolymerization reaction conditions include a reaction temperature of 170°C to 220°C.

[0019] Preferably, in step S1, the prepolymerization reaction is carried out at a reaction temperature of 200°C.

[0020] Optionally, in step S1, in the conditions of the prepolymerization reaction, the reaction time is selected from any value of 4h, 8h, 12h, 16h, 20h, 24h, 48h, or any range value therebetween.

[0021] Preferably, in step S1, the prepolymerization reaction conditions have a reaction time of 4 h to 16 h.

[0022] Preferably, in step S1, the prepolymerization reaction conditions have a reaction time of 8 hours.

[0023] Optionally, in step S1, the reactor used for the prepolymerization reaction is made of glass.

[0024] Optionally, in step S3, the conditions of the thermal polycondensation reaction include: a reaction temperature of 330° C. to 400° C., and a reaction time of 1 h to 8 h.

[0025] Optionally, in step S3, in the conditions of the thermal polycondensation reaction, the reaction temperature is selected from any value of 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or any range between the two.

[0026] Preferably, in step S3, the conditions for the thermal polycondensation reaction are that the reaction temperature is 370°C to 380°C.

[0027] Preferably, when the mesophase content in the obtained mesophase asphalt is 100%, the reaction temperature in the thermal polycondensation reaction is greater than or equal to 380°C.

[0028] Optionally, in step S3, in the conditions of the thermal polycondensation reaction, the reaction time is selected from any value of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, or any range between them.

[0029] Preferably, in step S3, the conditions for the thermal polycondensation reaction are that the reaction time is 2 h to 4 h.

[0030] Preferably, when the mesophase content in the prepared mesophase asphalt is 100%, the reaction time in the thermal polycondensation reaction conditions is greater than or equal to 3 hours.

[0031] Optionally, in step S3, the conditions of the thermal polycondensation reaction also include: a heating rate of 1°C / min to 5°C / min.

[0032] Optionally, in step S3, the reactor used for the thermal polycondensation reaction is a muffle furnace or a stainless steel reactor.

[0033] Optionally, in step S2, the alkali solution is selected from at least one of sodium carbonate solution, potassium carbonate solution, sodium hydroxide solution, and potassium hydroxide solution.

[0034] Preferably, the mass fraction of the alkali solution is 5%. At this mass concentration, the amount of the alkali solution used can be 70 to 80 times the volume of the metal-free superacid.

[0035] Optionally, the conditions for removing the catalyst and metal ions by washing with water include: adding water and repeatedly washing with water for more than three times to remove the catalyst and metal ions; the amount of water used in this step can be 0.5 to 2 times the volume of the alkali solution.

[0036] Optionally, the content of metal ions in the prepolymerization system after treatment in step S2 is less than 50 ppm.

[0037] Preferably, the content of metal ions in the prepolymerization system after the treatment in step S2 is less than 30 ppm.

[0038] Optionally, the conditions for removing small molecules by distillation include: adding water to the prepolymerization system from which the catalyst and metal ions are removed, and repeatedly distilling until no solid is precipitated in the condenser. This step is to remove unreacted monomers and light components in the system by steam stripping, and the amount of water used in this step can be 0.5 to 2 times the volume of the alkali solution.

[0039] Optionally, in step S1, the polycyclic aromatic hydrocarbons are selected from at least one of coal tar pitch, petroleum tar pitch, naphthalene, methylnaphthalene, anthracene, and phenanthrene.

[0040] Optionally, the condensed ring aromatic hydrocarbon is selected from at least one of naphthalene or coal tar pitch and petroleum asphalt having a softening point of 35 to 95°C.

[0041] Optionally, the inert atmosphere described in step S1 and the inert atmosphere described in step S3 are independently selected from at least one of nitrogen and argon.

[0042] According to another aspect of the present application, there is provided a mesophase asphalt prepared by the above method, wherein the optical morphology of the mesophase asphalt product is a wide-area structure.

[0043] Optionally, the intermediate phase presents a large-area flow texture.

[0044] Optionally, the mesophase is a fusion-type mesophase.

[0045] Optionally, the mesophase content in the mesophase asphalt is 1% to 100%.

[0046] Preferably, the mesophase content in the mesophase asphalt is 50% to 100%.

[0047] Optionally, the softening point of the mesophase asphalt is 230°C to 315°C.

[0048] Preferably, the softening point of the mesophase asphalt is 265°C to 315°C.

[0049] Optionally, the pyridine insoluble content (PI) of the mesophase asphalt is 51% to 75%.

[0050] Preferably, the pyridine insoluble content (PI) of the mesophase asphalt is 54% to 75%.

[0051] Preferably, the pyridine insoluble content (PI) of the mesophase pitch is 60% to 75%.

[0052] Preferably, when the mesophase content in the prepared mesophase asphalt is 100%, the pyridine insoluble matter content (PI) of the mesophase asphalt is greater than or equal to 65%.

[0053] Optionally, the hydrogen-to-carbon ratio (H / C) of the mesophase asphalt is 0.5 to 0.62.

[0054] Preferably, the hydrogen-to-carbon ratio (H / C) of the mesophase asphalt is 0.56 to 0.62.

[0055] Preferably, when the mesophase content in the prepared mesophase asphalt is 100%, the hydrogen-to-carbon ratio (H / C) of the mesophase asphalt is less than or equal to 0.58.

[0056] Optionally, the 002 crystal plane stacking height of the mesophase asphalt is 0.4085-0.4701 nm.

[0057] Optionally, the 002 crystal plane stacking height of the mesophase asphalt is 0.4147-0.4701 nm.

[0058] Preferably, when the mesophase content in the prepared mesophase asphalt is 100%, the 002 crystal plane stacking height of the mesophase asphalt is greater than or equal to 0.4147 nm.

[0059] Optionally, the ash content of the mesophase asphalt is less than 120 ppm.

[0060] Preferably, the ash content of the mesophase pitch is less than 100 ppm.

[0061] The mesophase asphalt prepared in this application has a low formation temperature, a short time, a high mesophase content, and basically no metal residue, and can be used for the subsequent preparation of high-performance asphalt-based carbon fibers. Compared with the metal catalytic system, the mesophase content obtained in this application is higher, and the mesophase distribution is more uniform, with a wide-area type structure.

[0062] The beneficial effects of this application include:

[0063] The method for preparing mesophase asphalt by metal-free superacid catalysis provided in the present application is that in the low-temperature polymerization reaction (prepolymerization reaction), the metal-free superacid has a strong acidity and is a strong proton acid, which can ionize to generate protons H + , has a strong proton-donating property and has a good catalytic effect in the reaction process. For example, trifluoromethanesulfonic acid catalyzes the reaction of aromatic naphthalene. The H +It reacts with naphthalene molecules to generate positively charged naphthalene cations. The charged naphthalene ions continue to react with naphthalene molecules in the system, and gradually generate naphthalene polymers with larger molecular weight through hydrogen transfer. At 200°C, trifluoromethanesulfonic acid can catalyze naphthalene to generate polymers with a degree of polymerization of 7. After the low-temperature polymerization reaction is completed, the metal-free superacid can be easily removed from the system by neutralization with alkali solution and washing with deionized water. It will not corrode the equipment for subsequent reactions. It has low requirements for experimental operation and high experimental safety. The product of catalyst removal has basically no metal residue and will not affect the subsequent high-temperature thermal polycondensation reaction. It is conducive to the synthesis of high-purity mesophase asphalt and the preparation of high-performance asphalt-based carbon fibers through further spinning, infusibility, carbonization and other treatments. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 These are polarized micrographs of the intermediate phase asphalt prepared at different reaction temperatures in Examples 17-19 and Examples 22 and 25 of the present application, wherein (a) 330°C-8h, (b) 350°C-8h, (c) 360°C-8h, (d) 370°C-8h, and (e) 380°C-8h.

[0065] Figure 2 These are polarized micrographs of the intermediate phase asphalt prepared at different reaction times in Examples 20-25 of the present application, wherein (a) 370℃-3h, (b) 370℃-5h, (c) 370℃-8h, (d) 380℃-3h, (e) 380℃-5h, and (f) 380℃-8h.

[0066] Figure 3 This is a polarized micrograph of the coal tar-based mesophase asphalt prepared in Example 37 of the present application.

[0067] Figure 4 Polarized micrographs of the mesophase pitch prepared by the aluminum chloride catalytic system at different temperatures in Comparative Examples 1 and 2, where (a) 360°C-8h; (b) 380°C-8h. DETAILED DESCRIPTION

[0068] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0069] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0070] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0071] The mesophase content is measured by polarizing microscopy and calculated based on the ratio of the bright area to the total area in the polarized image.

[0072] The hydrogen-to-carbon ratio (H / C) is determined in accordance with GB / T 476-2008;

[0074] Pyridine insoluble matter (PI) was determined according to GB / T 2293-2008 method;

[0075] The asphalt softening point (SP) is determined according to the method of GB / T 2294-2019;

[0076] Ash content is determined according to GB / T 2295-2008 method;

[0077] The metal content in the polymer was quantitatively analyzed using an inductively coupled plasma atomic emission spectrometer (SPECTRO ARCO) based on the JY / T015-1996 general rules for inductively coupled plasma atomic emission spectrometry.

[0078] In this application, the calculation formula of the embodiment is as follows:

[0079] Crystal plane (002) interlayer spacing formula: Where λ is the wavelength of the incident wave, and θ is the angle between the incident light and the (002) crystal plane, which can be obtained based on 2θ in the XRD spectrum;

[0080] Crystal plane (002) stacking height formula: Where λ is the wavelength of the incident wave, θ is the angle between the incident light and the (002) crystal plane, which can be obtained based on 2θ in the XRD spectrum, and β is the half-peak width of the (002) crystal plane diffraction peak, which can be obtained by fitting it using the origin software.

[0081] Example 1

[0082] The prepolymerization reaction of polycyclic aromatic hydrocarbons at low temperature is carried out by using metal-free superacid to catalyze the reaction. Alkali solution is added to the low-temperature prepolymerization reaction system to quench and neutralize the system, and then the catalyst, metal ions and small molecules are further removed:

[0083] The polymerization reaction was carried out in a 250 mL double-branch flask with a stirring magnet. The mouth and branch of the double-branch reaction flask were respectively equipped with a bottle stopper and a latex tube, and placed in a pumping system. It was baked with a liquefied gas spray gun under vacuum, and then filled with nitrogen after baking, and repeated three times. The ball bladder was placed in the pumping system, and vacuumed and filled with nitrogen were repeated three times to ensure that the ball bladder was filled with pure nitrogen;

[0084] Fill nitrogen from the branch pipe of the reaction bottle, add 50g of naphthalene from the bottle mouth, and then plug the bottle mouth. Fill nitrogen throughout the whole process, then clamp the branch pipe mouth filled with nitrogen with hemostatic forceps, connect the ball gallbladder to another branch pipe mouth, pump out the glass syringe three times, extract 1mL of fluorosulfonic acid, and inject it from the branch pipe mouth not connected to the ball gallbladder;

[0085] The reaction bottle is placed in an oil bath, adjusted to a reaction temperature of 80°C, stirred, and reacted for 8 hours. After the reaction bottle is cooled to room temperature, 75mL of a sodium carbonate solution with a mass fraction of 5% is added to the reaction system to remove the catalyst, and then an equal volume of deionized water is added, and the catalyst and metal ions are repeatedly washed with water to be removed. Since the sodium element in the system exists in the form of free ions, it can be removed by washing with water. 100mL of distilled water is added to a catalyst-free reaction bottle, which is placed in an oil bath, and the temperature is set to 110°C. Unreacted monomers are removed by steam stripping, and distillation is repeated many times until no solid is precipitated in the condenser tube, and the product in the reaction bottle is taken out and dried to obtain aromatic oligomers (naphthalene oligomers), which are weighed. The conversion rate of aromatic oligomers obtained under this condition is 5.4%, the softening point is 25°C, and the sodium content in the product is 22ppm.

[0086] Embodiments 2 to 16

[0087] The operating steps of the polymerization process for preparing aromatic oligomers in Examples 2 to 16 refer to Example 1, except that the raw material content and reaction conditions shown in Table 1 are different. The alkali solution for neutralizing trifluoromethanesulfonic acid in Examples 2, 3, and 5 is potassium carbonate, sodium hydroxide, and potassium hydroxide, respectively. The corresponding reaction conversion rate, product softening point, and test data of the metal content in the product are also shown in Table 1.

[0088] Examples 1-16 show the low temperature polymerization preparation process under different reaction temperatures, reaction times, catalyst types, catalyst dosages, types of condensed aromatic hydrocarbons, etc., and aromatic oligomers with different conversion rates and softening points can be obtained. It can be seen from the examples that by changing the conditions to achieve the adjustability of the aromatic oligomer structure, the metal content of the obtained product is less than 50 ppm, so that the ash content of the mesophase asphalt obtained by the subsequent thermal polycondensation is low.

[0089] The aromatic oligomers prepared in Examples 4 and 8 have a high conversion rate and a high softening point. Examples 11 and 15 respectively use petroleum asphalt and coal asphalt as raw materials for low temperature prepolymerization, and their conversion rate and softening point are high. It is beneficial to prepare a high-content mesophase asphalt by high-temperature thermal polycondensation, so it is used as a raw material for subsequent high-temperature thermal polycondensation reactions, as shown in Examples 17-38.

[0090] Table 1 Preparation of aromatic oligomers by different reaction raw materials and reaction conditions

[0091]

[0092] Embodiment 17

[0093] The aromatic oligomer product from which the catalyst has been removed is directly subjected to a high-temperature thermal polycondensation reaction to obtain a thermal polycondensation product:

[0094] The high-temperature polycondensation reaction was carried out in a stainless steel reactor. In a glove box with an argon atmosphere, 15 g of the aromatic oligomer (naphthalene oligomer) obtained in Example 4 was added to a stainless steel reactor with a capacity of 100 mL, vacuum silicone grease was applied to the threads above the reactor, the lid was closed, the reactor was taken out of the glove box, and it was placed in a muffle furnace, and the heating rate was set to 2 ° C / min, the reaction temperature was 330 ° C, and the reaction time was 8 h. After the reaction was completed, the reactor was taken out, cooled and allowed to stand for 12 h, the product was taken out of the reactor, weighed, and the conversion rate was calculated.

[0095] Select a suitable asphalt block and put it into the silicone mold, inject a certain amount of epoxy resin, and after it is completely cured, grind the sample block to a flat surface, and then polish it until the surface reaches a mirror effect. Under a polarizing microscope, the mesophase asphalt has a birefringent property and presents a bright color, while the isotropic asphalt product appears black.

[0096] Under these conditions, the optical morphology of the thermal polycondensation product is a very small amount of mesophase spheres, the mesophase content is 5.7%, the reaction conversion rate is 72%, the interlayer spacing of the (002) crystal plane is 0.3497nm, the crystal plane stacking height is 0.4251nm, the PI is 43%, the softening point is 195℃, the H / C is 0.72, and the ash content is 100ppm.

[0097] Embodiment 18

[0098] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 350°C and the reaction time is 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is intermediate phase spheres with a content of 10.1%, a reaction conversion rate of 67%, an interlayer spacing of the (002) crystal plane of 0.3481nm, a crystal plane stacking height of 0.4265nm, a PI of 46%, a softening point of 221°C, an H / C of 0.65, and an ash content of 100ppm.

[0099] Embodiment 19

[0100] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 360°C and the reaction time is 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is intermediate phase spheres with a content of 17.9%, a reaction conversion rate of 63.7%, an interlayer spacing of the (002) crystal plane of 0.3478nm, a crystal plane stacking height of 0.4358nm, a PI of 50%, a softening point of 233°C, an H / C of 0.65, and an ash content of 110ppm.

[0101] Embodiment 20

[0102] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 370°C and the reaction time is 3h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is intermediate phase spheres with a content of 37.7%, a reaction conversion rate of 61%, an interlayer spacing of the (002) crystal plane of 0.3473nm, a crystal plane stacking height of 0.4138nm, a PI of 45%, a softening point of 238°C, an H / C of 0.67, and an ash content of 102ppm.

[0103] Embodiment 21

[0104] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 370°C and the reaction time is 5h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 52.3%. The reaction conversion rate is 58%, the interlayer spacing of the (002) crystal plane is 0.3468nm, the crystal plane stacking height is 0.4085nm, the PI is 51%, the softening point is 270°C, the H / C is 0.62, and the ash content is 112ppm.

[0105] Embodiment 22

[0106] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 370°C and the reaction time is 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 64.5%, a reaction conversion rate of 55%, an interlayer spacing of the (002) crystal plane of 0.3465nm, a crystal plane stacking height of 0.4379nm, a PI of 54%, a softening point of 275°C, an H / C of 0.61, and an ash content of 106ppm.

[0107] Embodiment 23

[0108] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 380°C and the reaction time is 3h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 100%, a reaction conversion rate of 55%, an interlayer spacing of the (002) crystal plane of 0.3468nm, a crystal plane stacking height of 0.4147nm, a PI of 65%, a softening point of 280°C, an H / C of 0.58, and an ash content of 107ppm.

[0109] Embodiment 24

[0110] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 380°C and the reaction time is 5h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 100%, a reaction conversion rate of 53.5%, an interlayer spacing of the (002) crystal plane of 0.3454nm, a crystal plane stacking height of 0.4284nm, a PI of 66%, a softening point of 295°C, an H / C of 0.56, and an ash content of 112ppm.

[0111] Embodiment 25

[0112] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 380°C and the reaction time is 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 100%, a reaction conversion rate of 52.1%, an interlayer spacing of the (002) crystal plane of 0.3452nm, a crystal plane stacking height of 0.4701nm, a PI of 68%, a softening point of 305°C, an H / C of 0.56, and an ash content of 90ppm.

[0113] Embodiment 26

[0114] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that the reaction temperature is set to 400°C and the reaction is performed for 1 hour. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused intermediate phase with a content of 100%, a reaction conversion rate of 65%, an interlayer spacing of the (002) crystal plane of 0.3368nm, a crystal plane stacking height of 0.4655nm, a PI of 74%, a softening point of 315°C, an H / C of 0.53, and an ash content of 80ppm.

[0115] Embodiment 27

[0116] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (methyl naphthalene oligomer) prepared by Example 8 is added, the reaction temperature is set to 330°C, and the reaction is carried out for 5h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a very small amount of mesophase spheres, the mesophase content is 4.7%, the reaction conversion rate is 52%, the interlayer spacing of the (002) crystal plane is 0.3897nm, the crystal plane stacking height is 0.4105nm, the PI is 33%, the softening point is 180°C, the H / C is 0.76, and the ash content is 105ppm.

[0117] Embodiment 28

[0118] The operation steps of the polymerization process refer to Example 17, except that 15g of the aromatic oligomer (methylnaphthalene oligomer) prepared by Example 8 was added, the reaction temperature was set to 350°C, and the reaction was carried out for 8h. After the experiment, a thermal condensation product was obtained. Under this condition, the optical morphology of the thermal condensation product was mesophase globules with a content of 8.4%, a reaction conversion rate of 63%, an interlayer spacing of the (002) crystal plane of 0.3527nm, a crystal plane stacking height of 0.4121nm, a PI of 40%, a softening point of 211°C, an H / C of 0.69, and an ash content of 90ppm.

[0119] Embodiment 29

[0120] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (methylnaphthalene oligomer) prepared by Example 8 is added, the reaction temperature is set to 380°C, and the reaction is carried out for 3h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fusion-type mesophase with a content of 90%, a reaction conversion rate of 65%, an interlayer spacing of the (002) crystal plane of 0.3532nm, a crystal plane stacking height of 0.4135nm, a PI of 60%, a softening point of 270°C, an H / C of 0.61, and an ash content of 100ppm.

[0121] Embodiment 30

[0122] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic hydrocarbon oligomer (methyl naphthalene oligomer) prepared by Example 8 is added, the reaction temperature is set to 400°C, and the reaction is carried out for 1h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fused-type mesophase with a content of 100%, a reaction conversion rate of 68%, an interlayer spacing of the (002) crystal plane of 0.3448nm, a crystal plane stacking height of 0.4615nm, a PI of 70%, a softening point of 300°C, an H / C of 0.56, and an ash content of 70ppm.

[0123] Embodiment 31

[0124] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (petroleum asphalt oligomer) prepared by Example 11 is added, the reaction temperature is set to 330°C, and the reaction is carried out for 3h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a very small amount of mesophase spheres, the mesophase content is 10%, the reaction conversion rate is 77%, the interlayer spacing of the (002) crystal plane is 0.3321nm, the crystal plane stacking height is 0.4311nm, the PI is 56%, the softening point is 215°C, the H / C is 0.75, and the ash content is 90ppm.

[0125] Embodiment 32

[0126] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (petroleum asphalt oligomer) prepared by Example 11 is added, the reaction temperature is set to 350°C, and the reaction is carried out for 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is mesophase globules with a content of 21.1%, a reaction conversion rate of 70%, an interlayer spacing of the (002) crystal plane of 0.3391nm, a crystal plane stacking height of 0.4343nm, a PI of 55%, a softening point of 231°C, an H / C of 0.68, and an ash content of 95ppm.

[0127] Embodiment 33

[0128] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (petroleum asphalt oligomer) prepared by Example 11 is added, the reaction temperature is set to 360°C, and the reaction is carried out for 3h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is mesophase globules with a content of 18.1%, a reaction conversion rate of 65%, an interlayer spacing of the (002) crystal plane of 0.3471nm, a crystal plane stacking height of 0.4363nm, a PI of 52%, a softening point of 241°C, an H / C of 0.69, and an ash content of 85ppm.

[0129] Embodiment 34

[0130] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15g of the aromatic oligomer (petroleum asphalt oligomer) prepared by Example 11 is added, the reaction temperature is set to 400°C, and the reaction is carried out for 1h. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is a fusion-type mesophase with a content of 98%, a reaction conversion rate of 60%, an interlayer spacing of the (002) crystal plane of 0.3462nm, a crystal plane stacking height of 0.4624nm, a PI of 70%, a softening point of 303°C, an H / C of 0.56, and an ash content of 70ppm.

[0131] Embodiment 35

[0132] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15 g of the aromatic oligomer (coal tar oligomer) prepared by Example 15 is added, the reaction temperature is set to 330°C, and the reaction is carried out for 3 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is mesophase spheres with a content of 18%, a reaction conversion rate of 60%, an interlayer spacing of the (002) crystal plane of 0.3421 nm, a crystal plane stacking height of 0.4115 nm, a PI of 52%, a softening point of 223°C, an H / C of 0.55, and an ash content of 110 ppm.

[0133] Embodiment 36

[0134] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15 g of the aromatic oligomer (coal tar oligomer) prepared by Example 15 is added, the reaction temperature is set to 350°C, and the reaction is carried out for 5 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is mesophase spheres with a content of 32%, a reaction conversion rate of 63%, an interlayer spacing of the (002) crystal plane of 0.3421 nm, a crystal plane stacking height of 0.4215 nm, a PI of 54%, a softening point of 250°C, an H / C of 0.55, and an ash content of 98 ppm.

[0135] Embodiment 37

[0136] The operating steps of the high-temperature thermal polycondensation polymerization process refer to Example 17, except that 15 g of the aromatic oligomer (coal tar oligomer) prepared by Example 15 is added, the reaction temperature is set to 360°C, and the reaction is carried out for 8 hours. After the experiment, a thermal polycondensation product is obtained. Under this condition, the optical morphology of the thermal polycondensation product is large-sized intermediate phase spheres with a content of 48%. The reaction conversion rate is 57.3%, the interlayer spacing of the (002) crystal plane is 0.3274 nm, the crystal plane stacking height is 0.4553 nm, the PI is 65%, the softening point is 280°C, the H / C is 0.55, and the ash content is 113 ppm.

[0137] Embodiment 38

[0138] The operating steps of the polymerization process refer to Example 17, except that 15g of the aromatic oligomer (coal tar oligomer) prepared by Example 15 was added, the reaction temperature was set to 400°C, and the reaction was carried out for 1h. After the experiment, a thermal condensation product was obtained. Under this condition, the optical morphology of the thermal condensation product was a fusion-type mesophase with a content of 100%, a reaction conversion rate of 55%, an interlayer spacing of the (002) crystal plane of 0.3163nm, a crystal plane stacking height of 0.4651nm, a PI of 70%, a softening point of 310°C, an H / C of 0.51, and an ash content of 89ppm.

[0139] Comparative Example 1

[0140] The operation steps and reaction conditions of the polymerization process refer to Example 4, except that the catalyst is changed to aluminum chloride, and the addition amount is 5g. The obtained oligomer is subjected to high-temperature polycondensation according to Example 19. The optical morphology of the obtained thermal polycondensation product is mesophase spheres, the content of which is 13%, the reaction conversion rate is 68%, the interlayer spacing of the (002) crystal plane is 0.3518nm, the crystal plane stacking height is 0.4158nm, the PI is 55%, the softening point is 240℃, the H / C is 0.65, the aluminum content is 1.90%, and the ash content is 1.11%.

[0141] Comparative Example 2

[0142] The operation steps and reaction conditions of the polymerization process refer to Example 4, except that the catalyst is changed to aluminum chloride, and the addition amount is 5g. The obtained oligomer is subjected to high-temperature polycondensation according to Example 25. The optical morphology of the obtained thermal polycondensation product is a mosaic mesophase, the content of which is 55%, the reaction conversion rate is 52%, the interlayer spacing of the (002) crystal plane is 0.3411nm, the crystal plane stacking height is 0.4538nm, the PI is 70%, the softening point is 300℃, the H / C is 0.55, the aluminum content is 2.01%, and the ash content is 1.19%.

[0143] In summary, Figure 1 It can be seen that the mesophase asphalt begins to form at 330℃, and the shape is small spheres ( Figure 1 a), with the increase of temperature, the content of intermediate phase increases, reaching 15.3% at 360℃ ( Figure 1 c). When the temperature rises to 370℃, the fusion type intermediate phase begins to form ( Figure 1 d). When the polycondensation temperature is 380°C, the mesophase content reaches 100% ( Figure 1 e); 100% mesophase content can be obtained by thermal polycondensation for 3 hours ( Figure 2 d). In comparison, the aluminum chloride catalytic system has no mesophase formed at 330°C, the mesophase content is 13% at 360°C, and the mesophase content prepared by reacting for 8 hours at 380°C is 55%, which is a mosaic mesophase. This shows that the thermal polycondensation activity of the catalytic system of the present application is higher than that of the aluminum chloride catalytic system, the temperature for forming the mesophase is low, the rate is fast, and the mesophase content is high.

[0144] The system of the present application can catalyze the preparation of mesophase pitch from various other condensed ring systems, including coal pitch, petroleum pitch, naphthalene, methylnaphthalene, etc. Figure 3 As shown, catalytic coal tar pitch can be used to prepare coal tar pitch-based mesophase, and high-temperature thermal polycondensation at 360°C for 8 hours can obtain larger mesophase pellets with a mesophase content of 48%, which is higher than the mesophase content of naphthalene asphalt.

[0145] Comparing Comparative Example 1, Example 4 and Example 19, at a lower polycondensation temperature, the metal content of the product obtained by the present application is very small, 23 ppm, compared with the aluminum chloride catalyst system, resulting in an extremely low ash content of 110 ppm. The conversion rate and softening point under the same preparation conditions are equivalent, and the intermediate phase content obtained by the present application is high (the trifluoromethanesulfonic acid catalyst system is as Figure 1 c: 17.9%; aluminum chloride catalytic system as Figure 4 a: 13%).

[0146] Comparing Comparative Example 2, Example 4 and Example 25, at a higher polycondensation temperature, the metal content of the product obtained by the present application is very small, 23 ppm, compared with the aluminum chloride catalyst system, resulting in an extremely low ash content of 90 ppm. The conversion rate and softening point under the same preparation conditions are equivalent, and the mesophase content obtained by the present application is higher, and it is a wide-area mesophase with a more uniform distribution (such as the trifluoromethanesulfonic acid catalyst system Figure 1 e: 100%; aluminum chloride catalytic system as Figure 4 b: 55%).

[0147] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing mesophase asphalt using metal-free superacid catalysis, characterized in that: The steps include: S1. In an inactive atmosphere, a metal-free superacid is contacted with a condensed aromatic hydrocarbon as a catalyst to carry out a prepolymerization reaction to obtain a prepolymerization system; S2, adding alkali solution to the prepolymerization system of step S1 until the prepolymerization system is neutral, then washing with water to remove the catalyst and metal ions, and distilling to remove small molecules; S3. In an inert atmosphere, placing the prepolymerization system treated in step S2 in a closed container to carry out a thermal polycondensation reaction to obtain the mesophase asphalt.

2. The method according to claim 1, characterized in that In step S1, the metal-free superacid is selected from at least one of fluorosulfonic acid, chlorosulfonic acid, trifluoromethanesulfonic acid, and carborane acid; Preferably, the amount of the metal-free superacid is 3% to 30% by weight of the condensed aromatic hydrocarbon.

3. The method according to claim 1, characterized in that In step S1, the conditions of the prepolymerization reaction include: reaction temperature of 80°C to 250°C, and reaction time of 4h to 48h.

4. The method according to claim 1, characterized in that In step S3, the conditions of the thermal polycondensation reaction include: a reaction temperature of 330° C. to 400° C., and a reaction time of 1 h to 8 h.

5. The method according to claim 1, characterized in that In step S2, the alkali solution is selected from at least one of a sodium carbonate solution, a potassium carbonate solution, a sodium hydroxide solution, and a potassium hydroxide solution; Preferably, the content of metal ions in the prepolymerization system after treatment in step S2 is less than 50 ppm; Preferably, the conditions for removing small molecules by distillation include: adding water to the prepolymerization system from which the catalyst and metal ions are removed, and repeatedly distilling until no solid is precipitated in the condenser.

6. The method according to claim 1, characterized in that In step S1, the condensed ring aromatic hydrocarbons are selected from at least one of coal tar pitch, petroleum tar pitch, naphthalene, methylnaphthalene, anthracene and phenanthrene.

7. The method according to claim 1, characterized in that The inert atmosphere in step S1 and the inert atmosphere in step S3 are independently selected from at least one of nitrogen and argon.

8. The mesophase asphalt prepared by the method according to any one of claims 1 to 7, characterized in that: The optical morphology of the mesophase asphalt product is a wide-area structure.

9. The mesophase pitch according to claim 8, characterized in that The mesophase content in the mesophase asphalt is 1% to 100%; Preferably, the mesophase content in the mesophase asphalt is 50% to 100%.

10. The mesophase pitch according to claim 8, characterized in that The softening point of the mesophase asphalt is 230°C to 315°C; Preferably, the softening point of the mesophase asphalt is 265°C to 315°C; Preferably, the pyridine insoluble content of the mesophase asphalt is 51% to 75%; Preferably, the hydrogen-to-carbon ratio of the mesophase asphalt is 0.5 to 0.62; Preferably, the 002 crystal plane stacking height of the mesophase asphalt is 0.4085 to 0.4701 nm; Preferably, the ash content of the mesophase pitch is less than 120 ppm.